Mobilization against forced domestic work in Peru - Schalkowski, Nicola (Frontiers in Sociology, 2025)
Organized domestic workers have recently been at the forefront of political campaigns in Peru to promote legislative reforms concerning forced labor. This empirical case study investigates how the international labor norm concerning forced labor is disseminated, appropriated and politically mobilized at the national level. It thereby examines the dynamics and cultural embedding of the appropriation process and its implications for labor regulation, policy responses and trade union actions. The research delves into the ways and spaces in which international and national actors, the International Labour Organisation and national domestic workers’ trade unions, translate the international norms into their local context, adapt and negotiate them. I argue that the mobilization against forced domestic labor is embedded in the period of reconfiguration of the domestic work sector in Peru and that it is oriented toward internationally institutionalized categorizations and indicators. By employing the theoretical lens of vernacularization, a contextualizing examination of the labor policy actors, their positions and knowledge bases, as well as an analysis of decisive moments, spaces, technologies and developments of communicative actions, enables a sociological understanding of the emergence and manifestation of the mobilization against forced domestic work. The process of vernacularization creates a localized version of international norms that retains elements of the original while incorporating local specificities in the implementation. It creates a space where different forms of knowledge interact – local knowledge and transnational technicized knowledge. This research adds a nuanced understanding of the intersection between internationalization of ‘universal’ labor standards, knowledge production, and trade union mobilization within a feminized and racialized sector.